A Simple HPLC-UV Method for the Determination of Glutathione in PC-12 Cells. (4th April 2016) - Appala, Raju N.; Chigurupati, Sridevi; Appala, Raju V. V. S. S.; Krishnan Selvarajan, Kesavanarayanan; Islam Mohammad, Jahidul
Abstract : A highly sensitive and simple HPLC-UV method was developed and validated for the assay of glutathione (GSH) in PC-12 cells. Glutathione is a major intracellular antioxidant having multiple biological effects, best known for its cytoprotective effects against cell damage from reactive oxygen species and toxic reactive metabolites and regulating the cellular redox homeostasis. Due to its own sulfhydryl (SH) group, GSH readily reacts with Ellman's reagent to form a stable dimer which allows for quantitative estimation of GSH in biological systems by UV detection. The separation was achieved using a C8 column with a mobile phase consisting of phosphate buffer adjusted to pH 2.5 (mobile phase A) and acetonitrile (mobile phase B), running in a segmented gradient manner at a flow rate of 0.8 mL/min, and UV detection was performed at 280 nm. The developed HPLC-UV method was validated with respect to precision, accuracy, robustness, and linearity within a range of 1–20  μ g/mL. Limit of detection (LOD) and limit of quantification (LOQ) were 0.05 and 0.1  μ g/mL, respectively. Furthermore, the method shows the applicability for monitoring the oxidative stress in PC-12 cells.